Optimizing Peanut Seed Storage and Quality through Biological Coating with IAA-Producing Enterobacter kobei and Agrobacterium radiobacter - Prommayakul, Saralee; Inthasan, Jiraporn; Viroonrat, Vassana; Kangsopa, Jakkrapong (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Peanut seeds are prone to deterioration during storage due to their high oil content, which makes them susceptible to lipid oxidation, leading to the formation of free radicals that accelerate cellular degradation. This process can alter the seed structure and nutrient reserves, ultimately reducing seed viability and lowering germination rates over prolonged storage periods. Therefore, seed coating techniques are crucial in mitigating seed deterioration, particularly through the application of IAA-producing bacteria that enhance seed quality and slow down the degradation process. This study aimed to evaluate the effects of coating peanut seeds with Enterobacter kobei and Agrobacterium radiobacter at a concentration of 10⁷ CFU/mL on seed quality during a 4-month storage period under controlled (4°C with 50% RH) and ambient conditions (27°C±2 with 70%±5 RH). The results demonstrated that seeds coated with E. kobei at 107 CFU/mL and A. radiobacter at 107 CFU/mL exhibited significantly higher germination percentages, increased germination speed, and reduced mean germination time compared to non-coated seeds. These effects were particularly pronounced under controlled conditions, where coated seeds maintained superior quality and promoted seedling growth throughout the storage period. Furthermore, E. kobei at 107 CFU/mL and A. radiobacter at 107 CFU/mL significantly improved the shoot and root length as well as the shoot and root dry weight of peanut seedlings compared to the seedlings of non-coated seeds. Considering the overall results, it can be concluded that seed coating with A. radiobacter at 107 CFU/mL exhibited the most substantial enhancement in seed quality, making it the recommended approach for improving peanut seed germination, vigor, and seedling growth during a 4-month storage period. Notably, the coated seeds maintained high germination percentage and vigor throughout the entire 4-month storage duration, indicating extended seed longevity under both controlled and ambient conditions.